Alveolar soft part sarcoma. (10th April 2014) - Singh, Aarti; Gupta, Sunita; Ghosh, Sujoy; Yuwanati, Monal Bhaurao
Abstract : Alveolar soft part sarcoma (ASPS) is a rare form of soft tissue sarcoma and is most often seen in adolescents and young adults. Despite its unique histology and well-characterised genetic translocation, many questions remain regarding the pathogenesis and treatment of this tumour type. Surgical excision of the primary tumour and pulmonary metastases has resulted in prolonged survival of some patients while the benefit of adjuvant chemotherapy and/or radiotherapy has been disputed. A 35-year-old woman presented with a tumour in the right leg and right side of the mandible along with active metastasis to lungs and multiple skeletal sites.